Integrating Educational Strategies into Tax Management: A Study on Individual Taxpayer Compliance - Oni Oktavia; Rizki Syafril (Journal of Educational Management Research, 2025)
This study aims to examine the compliance of individual taxpayers in filing their Annual Tax Return (SPT) within a self-assessment taxation system. The research employs a qualitative method with a descriptive approach, utilizing in-depth interviews and observations involving tax officers, tax consultants, and registered taxpayers. The findings reveal that most taxpayer compliance in the area is instrumental, driven by concerns over administrative sanctions, institutional oversight, and pressure near the reporting deadline. Meanwhile, only a small portion of taxpayers exhibit normative compliance based on personal awareness and responsibility. The limitation of this study lies in its geographic scope, which is confined to a specific region, and the use of purposive sampling, which restricts the generalizability of the findings. This research provides valuable insights into the dynamics of compliance within a self-assessment taxation system and underscores the need for educational and interpersonal approaches to foster long-term compliance.